2018
DOI: 10.1016/j.jconrel.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Physical blood-brain barrier disruption induced by focused ultrasound does not overcome the transporter-mediated efflux of erlotinib

Abstract: Overcoming the efflux mediated by ATP-binding cassette (ABC) transporters at the blood-brain barrier (BBB) remains a challenge for the delivery of small molecule tyrosine kinase inhibitors (TKIs) such as erlotinib to the brain. Inhibition of ABCB1 and ABCG2 at the mouse BBB improved the BBB permeation of erlotinib but could not be achieved in humans. BBB disruption induced by focused ultrasound (FUS) was investigated as a strategy to overcome the efflux transport of erlotinib in vivo. In rats, FUS combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 82 publications
2
36
0
Order By: Relevance
“…Sonodynamic therapy using the 5-aminolevulinic acid (5-ALA) has been combined with transcranial MRI-guided focused ultrasound (MRgFUS) and real-time MRI thermometry to monitor and optimize the therapy in a rat brain tumor model, achieving an improved survival time [422]. Nevertheless, in a recent study, physical BBB disruption provoked by MB-enhanced FUS did not impact the brain kinetics of 11 C-erlotinib, while elacridar did increased its brain penetration (with or without FUS), indicating that erlotinib delivery into the brain is governed by ABC transporters efflux and not by the physical integrity of the brain and suggesting that the selection of the chemotherapeutic for FUS is critical, as this strategy may not overcome the ABC-mediated efflux [273].…”
Section: Bbb Disruption: Osmotic Disruption and Ultrasound-enhanced Dmentioning
confidence: 87%
See 2 more Smart Citations
“…Sonodynamic therapy using the 5-aminolevulinic acid (5-ALA) has been combined with transcranial MRI-guided focused ultrasound (MRgFUS) and real-time MRI thermometry to monitor and optimize the therapy in a rat brain tumor model, achieving an improved survival time [422]. Nevertheless, in a recent study, physical BBB disruption provoked by MB-enhanced FUS did not impact the brain kinetics of 11 C-erlotinib, while elacridar did increased its brain penetration (with or without FUS), indicating that erlotinib delivery into the brain is governed by ABC transporters efflux and not by the physical integrity of the brain and suggesting that the selection of the chemotherapeutic for FUS is critical, as this strategy may not overcome the ABC-mediated efflux [273].…”
Section: Bbb Disruption: Osmotic Disruption and Ultrasound-enhanced Dmentioning
confidence: 87%
“…PET was recently employed to validate the permeability and transporter function of a human iPSCs BBB model [172] and the evaluation of ABC transporter-humanized mice models [238,270]. Importantly, it has been used to evaluate drug delivery strategies, such as inhibition [250,251] or focused ultrasounds [273] (see Section 6.5 for details).…”
Section: Imaging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL IIE+L BCRP), which are responsible for the efflux of many drugs, including TKIs [20]. However, research has proven that TKIs, such as lapatinib, erlotinib, gefitinib, afatinib, crizotinib, and alectinib, in combination with cytotoxic drugs or alone, are potent in reducing the development of CNS tumors [21][22][23][24][25][26]. Lapatinib is a substrate for P-gp and BCRP, which are abundantly expressed in the intestine, liver, kidney and BBB [27].…”
Section: Time [H]mentioning
confidence: 99%
“…The inhibited transporters affect the absorption of TKIs in the intestine, their hepatic and renal excretion and penetration through the BBB. The expression levels and activity of P-gp and BCRP are strongly associated with the limited distribution of most TKIs to the BT [22]. Research has shown that brain accumulation of axitinib, cediranib and crizotinib depends mainly on ABCB1 activity, whereas the brain disposition of sorafenib is predominantly influenced by the ABCG2 protein [23].…”
Section: Time [H]mentioning
confidence: 99%